ETC L2 Meteo from Svartberget, 2018-12-31–2025-12-31 - Matthias Peichl; Mats Nilsson; Eric Larmanou; Paul Smith; Per Marklund; Giuseppe De Simon; Pernilla Lofvenius; Rowan Dignam; Jutta Holst; Meelis Molder; Tommy Andersson; Fabio Boschetti; et al. (Integrated Carbon Observation System, 2026)
Half-hourly meteorological variables with values aggregated spatially (e.g. one single soil temperature value per layer) calculated by the ICOS ETC starting from the single sensor half-hourly measurements.
Peichl, M., Nilsson, M., Larmanou, E., Smith, P., Marklund, P., De Simon, G., Lofvenius, P., Dignam, R., Holst, J., Molder, M., Andersson, T., Boschetti, F., Kozii, N., Linderson, M., Ottosson-Löfvenius, M. (2026). ETC L2 Meteo from Svartberget, 2018-12-31–2025-12-31, ICOS RI, https://hdl.handle.net/11676/gzeLiX_AZKcwj3Bqpp73clsC
Keywords: Ecosystem Thematic Centre; ICOS; meteo; time instant, UTC; time instant, UTC; time instant, local non-DST time; time instant, local non-DST time; air temperature; air temperature; relative humidity; relative humidity; atmospheric pressure; atmospheric pressure; outgoing shortwave radiation; outgoing shortwave radiation; incoming long-wave radiation, net radiometer; incoming long-wave radiation, net radiometer; outgoing long-wave radiation, net radiometer; outgoing long-wave radiation, net radiometer; photosynthetic photon flux density incoming; photosynthetic photon flux density incoming; photosynthetic photon flux density outgoing; photosynthetic photon flux density outgoing; photosynthetic photon flux density diffuse; photosynthetic photon flux density diffuse; precipitation (total); precipitation (total); snow depth; snow depth; soil heat flux; soil heat flux; soil temperature; soil temperature; water table depth; water table depth; volumetric soil water content; volumetric soil water content; vapour pressure deficit; vapour pressure deficit; incoming shortwave radiation; incoming shortwave radiation; photosynthetic photon flux density below canopy incoming; photosynthetic photon flux density below canopy incoming; wind speed; wind speed; wind direction; wind direction; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap